The Influence Of Compensation And Motivation on The Performance of PT Master Kuliner Indonesia Employees In Sawangan Depok - Kemas Vivi Andayani; Zhania Adzani (Indonesian Development of Economics and Administration Journal, 2023)
This research aims to determine the effect of compensation and motivation on the performance of employees of PT Master Kuliner Indonesia located in Sawangan Depok. The research method used is a quantitative method. The population in this study was 50 respondents, who were employees of PT Master Kuliner Indonesia located in Sawangan Depok. The sampling technique uses Probability Sampling (Simple Random Sampling) and Non-Probability Sampling (Quaota Sampling) techniques. The analysis in this research used the SPSS (Statistical Package for Social Science) software program version 26.0. Meanwhile, the analysis techniques using analysis are validity and reliability tests, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test and autocorrelation test), multiple linear regression test, multiple correlation coefficient test, coefficient of determination test and hypothesis test, namely the t test ( partial test) and F test (simultaneous test). The results of the t test of compensation on performance show that the value of t count > t table value and is significant < 0.05, namely 3.860 > 2.011 and the significant value is 0.000 < 0.05, so it can be concluded that H01 is rejected and Ha1 is accepted, which means there is an influence of compensation on performance employees partially. The results of the t test of motivation on employee performance show that the t count > t table value is significant < 0.05, namely 2.955 > 2.011 and the significant value is 0.011 < 0.05, so it can be concluded that H02 is rejected and Ha2 is accepted, which means there is an influence of motivation on performance. employees partially and the results of the F test of compensation and motivation simultaneously on employee performance show that the F count > F table value is significant < 0.05, namely 18,767 > 4.047 and the significant value is 0.000 < 0.05, so it can be concluded that H0 3 is rejected and Ha 3 is accepted, which means there is a simultaneous influence of compensation and motivation on employee performance. Based on the results of the coefficient of determination, the Adjusted R Square value is 0.444 or 44.4%. This means that the compensation variable (X1) and motivation variable (X2) are able to explain the magnitude of the influence on the Employee Performance variable (Y), namely 44.4%, while the remaining 63.6% can be influenced by other variables